Pengaruh Gender, Kompleksitas Tugas, Tekanan Ketaatan, Pengalaman Auditor Terhadap Audit Judgement - Pektra, Stacia; Kurnia, Ratnawati (Universitas Multimedia Nusantara, 2015)
The purpose of this research was to examine the impact of gender, task complexity, obedience pressure, experience of auditors towards Audit Judgement. The object the auditors who works in the Public Accountant firms in Jakarta and Tangerang which have at least 3 years experience or have position as senior auditor. Data that had been analyzed were 110 questionnaires and the data were primer data. The type in this research is causal study and the sampling techniques that used is convenience sampling. The method that used is multiple regression analysis. The data that had been used from the entire questionnaires were valid. Reliability test results show questionnaires in this study is reliable. Normality test results showed all variables were normally distributed. Data used indicate the absence of the classical assumption of heteroscedasticity and non-occurrence of symptoms multicoloniarity between variables. Hypothesis test results indicate a strong correlation between variables and adjusted R-square value of 34.6%. In partial test only complexity of tasks that affect theentire audit judgment and all variables influential simultaneously. Keywords: Audit Experience, Audit Judgement, Gender, Obedience Pressure, Task Complexity